Association of Socio-Demographic and Climatic Factors with the Duration of Hospital Stay of Under-Five Children with Severe Pneumonia in Urban Bangladesh: An Observational Study - K. A. T. M. Ehsanul Huq; Michiko Moriyama; Ryota Matsuyama; Md Moshiur Rahman; Reo Kawano; Mohammod Jobayer Chisti; Md Tariqujjaman; Nur Haque Alam (MDPI AG, 2021)
Severe pneumonia is one of the leading contributors to morbidity and deaths among hospitalized under-five children. We aimed to assess the association of the socio-demographic characteristics of the patients and the climatic factors with the length of hospital stay (LoS) of under-five children with severe pneumonia managed at urban hospitals in Bangladesh. We extracted relevant data from a clinical trial, as well as collecting data on daily temperature, humidity, and rainfall from the Meteorological Department of Bangladesh for the entire study period (February 2016 to February 2019). We analyzed the data of 944 children with a generalized linear model using gamma distribution. The average duration of the hospitalization of the children was 5.4 ± 2.4 days. In the multivariate analysis using adjusted estimation of duration (beta; β), extended LoS showed remarkably positive associations regarding three variables: the number of household family members (β: 1.020, 95% confidence intervals (CI): 1.005-1.036, p = 0.010), humidity variation (β: 1.040, 95% Cl: 1.029-1.052, p < 0.001), and rainfall variation (β: 1.014, 95% Cl: 1.008-1.019), p < 0.001). There was also a significant negative association with LoS for children's age (β: 0.996, 95% Cl: 0.994-0.999, p = 0.006), well-nourishment (β: 0.936, 95% Cl: 0.881-0.994, p = 0.031), and average rainfall (β: 0.980, 95% Cl: 0.973-0.987, p < 0.001). The results suggest that the LoS of children admitted to the urban hospitals of Bangladesh with severe pneumonia is associated with certain socio-demographic characteristics of patients, and the average rainfall with variation in humidity and rainfall.